تقويــة ســبيكة (الالمنيــوم-ســليكون) باضــافة مـــواد ســـيراميكية - حســين عتيــوي علــي; مصطفى كمــال حمــزة (Journal of Engineering and Sustainable Development, 2007)
This study is concerned with the effect of adding two kinds of ceramic materials on the mechanical properties of (Al -7% Si) alloy, which are silicon carbide of particle size (25μm > P.S ≥ 0.1μm) and boron carbide of particle size (20μm > P.S ≥ 0.1μm) and adding them to the alloy with weight ratios (0.2,0.4,0.6,0.8,1 %). Stirring casting method has been used to make composite material by using vortex technique which is used to pull the particles to inside the melted metals and distributed them homogenously. After that solution treatment was done to the samples at (520ºC) and artificial ageing at (170ºC) in different times. It has been noticed that the values of hardness are increased with aging time of the base alloy and reached its highest value after (8hr).Mechanical tests were done to the original alloy and the composite material at the maximum hardness value and represented by tensile, hardness, and wear tests. It was found that the hardness value is increased with increment of the amount of added particles; also the increment in the hardness of the alloy which is reinforced with boron carbide is more than that reinforced with silicon carbide. Regarding the tensile test, results shown that the strength and yield resistance of the composite material are more than that in the base alloy and these values are increased with increasing of the added particles and they reached maximum values at (0.6%). Then they are decreased....